Numerical study of fully baffled Super-X L-mode discharges on TCV. (March 2023) - Meineri, C.; Muscente, P.; Theiler, C.; Galassi, D.; ,; ,
Abstract: We present a numerical study of three fully baffled L-mode TCV discharges with three different values of the outer strike-point major radius/total flux expansion, showing that the beneficial effect of large strike point radius is partially screened in these experiments by a not perfectly equalized neutral divertor trapping. The assessment of the SOL and divertor plasma conditions is made with the SolEdge2D-EIRENE plasma edge code. The simulation results show that artificially increasing the outer baffle length induces a 30% decrease in the neutral particles influx at the last closed surface LCFS and main SOL plasma in scenarios with large strike point radius. This causes a drastic reduction of plasma temperature on the divertor target in these cases, approaching the two point model (TPM) expectation. Instead a longer outer baffle is predicted to be negligible for the smallest strike point radius, where the neutrals are already well confined with the actual geometry of the baffle. This numerical work illustrated the different challenges to face during the experiments to retrieve the full benefits expected from total flux expansion, most of it related to geometry and magnetic wall alignment, giving some hints to reduce the difference between the ideal experiment and the real one. Highlights: The TCV Super-X experiments show a disagreement with the expected theory. The effect of Super-X is partially screened by a not perfect neutral trapping. A longer baffle improves the agreement between the edge modelling and the theory.